Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Deconstructing soil detachment: integrated assessment of soil properties, root characteristics, and hydraulics under diverse land uses on the Chinese loess plateau - JianFang Wang; JiaMing Li; GuoBin Liu; WeiWei Ma; Bing Wang (CATENA, 2026)

Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Amplification-free electrochemiluminescence biosensors based on peptide-templated gold nanocluster and CRISPR-Cas12a for Mycobacterium tuberculosis IS6110 detection - Lingjun Cheng; Qingmei Yang; Yuanyuan Yang; Yufeng Wang; Qingfei He; Zhiyan Zou; Canping Su; Jiaming Chen; Yinhuan Liu; Guolin Hong (Analytica Chimica Acta, 2026)

Amphibian skin peptides: Diversity, biological functions, and research progress - Zihui Chen; Qing Pan; Jiaming Zhang; Ren Lai; Wenhua Yu; Aili Wang (Toxicon, 2026)

Synergistic effects of spray pre-cooling and prochloraz treatment on postharvest quality maintenance of 'Guiwei' litchi - Jiaming Guo; Jianye Wang; Dinghe Wu; Peng Guo; Zhiwu Ding; Jingrui Meng; Haoran Dai; Jiahang Qiao; Zilong Deng; Enli Lü (Postharvest Biology and Technology, 2026)

Machine learning prediction and interpretability of sewage sludge pyrolysis gas yield and composition - Yi Xiao; Jingyi Li; Qigui Niu; Tianxue Yang; Jiaming Zhao; Xiaowei Wang; Dongyang Li (Journal of Environmental Chemical Engineering, 2026)

LvBlimp1 and LvHes1 coregulate the function of macrophage-like phagocytes in shrimp hemolymph - Jiaming Liu; Yaohui Chen; Wenyong Jiang; Zhiyao Lu; Nuo Lin; Qingyun Liu; Xiuli Chen; Yongzhen Zhao; Fan Wang (Fish & Shellfish Immunology, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Carbide-induced high dispersion and electronic regulation of Pt species toward stable propane dehydrogenation - Xiaonan Wang; Jiaming Ma; Jun Li; Haoyu Yan; Zhikai Yang; Bo Jiang; Xiao Zhang (Chemical Engineering Journal, 2026)

Microbes Isolated from Ailanthus altissima Leaves Contribute to Samia cynthia’s Tolerance to the Toxic Quassinoid Diterpenoid - Jiaming Zhang; Juan Hua; Yangyang Wang; Jiayi Liu; Zhen Yang; Yanqun Liu; Shihong Luo (Journal of Chemical Ecology, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Cyclic biomineralization by incorporating iron-oxidizing and sulfate-reducing microorganisms for sustainable iron removal and sulfur recovery from acid mine drainage: Efficiency and mechanism - Xingjie Wang; Ling Liu; Yuxuan Yang; Jiaming Du; Liyuan Ma; Jie Tang; Peng Liu; Jianwei Zhou (Minerals Engineering, 2026)

Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

DCMArb: Decoupled-Collaborative Mamba for Arbitrary-scale Hyperspectral Super-resolution - Shuo Wang; Mi Wang; Jiaming Wang; Zhenbei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

Selective infrared thermal modulation device based on mixed-crystalline WO3 and electrochromic dynamic regulation technology - Jiaming Yang; Mengying Wang; Abderaouf DJEFFAL; Shukai Wang; Zheng Meng; Xinru Xu; Xungang Diao (Chemical Engineering Journal, 2026)

Air plasma constructing multi-defects in NiFe metal-organic frameworks for enhanced electrocatalysis - Jiaming Zhao; Yilin Li; Xuchen Miao; Yuanbo Wang; Xingyun Li; Yubao Liu; Zhiliang Liu; Guoling Li (Chemical Engineering Journal, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Experimental study of condensation induced water hammer caused by the accumulation of condensate water in the steam pipeline - Minchao Liang; Jiaming Zhao; Jiarui Zhang; Rongyang Xue; Yili Yang; Wentao Guo; Shengfei Wang (Annals of Nuclear Energy, 2026)

Machine learning-assisted smartphone fluorescence sensing for ultrasensitive and point-of-care testing of acid phosphatase - Fusheng Zhong; Jiaming Zhang; Huaxi Ruan; Tonglong Yang; Jinbo Cao; Liangliang Peng; Jinhui Liu; Qingqing Deng; Li Wang (Analytica Chimica Acta, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Dynamic Tensile Properties and Fracture Evolution Characteristics of Ice-Filled Fissured Red Sandstone - Jiaming Wang; Zilong Zhou; Lingyi Zeng; Jun Hou; Zhen Wang (Rock Mechanics and Rock Engineering, 2026)

Exploring the carbon reduction effects of different rooftop utilization modes for public buildings - A regional perspective - Peng Wang; Yihao Yang; Jiawen Liu; Xiangyu Min; Lei Huang; Jiaming Wang (Sustainable Cities and Society, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

Revealing the antioxidant potential of Artemisia integrifolia L.: Integrated discovery of bioactive compounds via UHPLC-DPPH and activation of the Nrf2/HO-1 signaling pathway - Huimin Li; Qian Gao; Yijin Wu; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Inner-body governing mechanisms for shear-driven gas leakage flow over a ventilated supercavity - Wang Zou; Jiaming Wang; Liuxuan Li; Chongguang Wang; Hanyu Gan; Hanxu Qiu (Ocean Engineering, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Auxiliary fermentation with Pediococcus acidilactici C1 reshapes flavor formation in sufu: An integrated metagenomic, flavoromic and non-targeted metabolomic deciphering - Chen Chen; Jiaming Li; Feng Wang; Mei Cheng; Tao Sheng; Zahoor Ahmed; Jingwei Hu; Yibin Zhou (Food Chemistry, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Targeted “ROS storm” in hypoxic periodontitis: A self-enhanced SDT/CDT synergistic platform based on triple-enzymatic Cu-Mo bimetallic nanozyme - Wei Wu; Tong Xu; Kehan Wu; Lilong Yang; Jiaming Wang; Kaidi Liang; Dan Yang; Piaoping Yang; Narisu Hu (Chemical Engineering Journal, 2026)

Maternal Stress During Pregnancy Induces Higher Anxiety-Like Behavior in Male Mice Offspring Under Acute Stress by Upregulating CRF/CRFR1 and Driving Time-Specific Activation of the MHb-IPN Circuit - Yujie Wang; Jiajia Zhao; Yueyang Wang; Zhixin Du; Li Wang; Zibo Ma; Siyang Sun; Xinyang Qu; Xiaohan Geng; Jiaming Yan; Liping Yang; Junlin Hou (Neuroscience Bulletin, 2026)

Bioavailable heavy metals drive spatial reassembly and functional reprogramming of soil bacterial communities in electroplating-impacted farmland - Yaoben Lin; Jiaming Zhao; Dong Wang; Xinliang Wang (Applied Soil Ecology, 2026)

A bibliometric analysis of global duckweed research (2015–2025): research trends, international collaborations, and emerging themes - Jiaming Wang; Zhenghong Peng; Zuoyue Duan; Yaojun Zhou; Hongling Zhu; Shijun You; Zhiyi Peng; Mengni Shi; Qulian Guo; Wenjun Liu; Ling Guo (Hydrobiologia, 2026)

Synergistic architecture and dynamic adaptability in heterogeneous catalysts for CO2 hydrogenation - Jiao Liu; Xingyi Cen; Jiaming Lin; Junrong Yue; Duo Sun; Fang Wang (Journal of Environmental Sciences, 2026)

A significantly enhanced Cu+/Cu0 catalytic active structure via the electronic effect of K for methyl glycolate synthesis - Xiaoxiao Zheng; Jiaming Wang; Peipei Lei; Qihong Xue; Xian Kan; Jiangang Chen (Chemical Engineering Journal, 2026)

A novel approach to distinguish the respective contributions of galvanic effect and reactive oxygen species on sulfide mineral dissolution: Insights from stibnite and pyrite - Xiaoqian Li; Jingxuan Qiu; Xingjie Wang; Jiaming Du; Deng Liu; Chun Li; Hongmei Wang; Liyuan Ma (Chemical Geology, 2026)

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

Dynamic Mechanical Response and Stress Wave Propagation Characteristics of Red Sandstone with Ice-Filled Joints of Varying Thicknesses - Zilong Zhou; Jiaming Wang; Zhen Wang; Yingxin Zhou; Ziyu Wang (Rock Mechanics and Rock Engineering, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Quantifying tire wear particle dynamics: insights from a hydrological-based material flow analysis in urban watersheds - Lebing Ying; Shujie Xu; Jiaming Wang; Shu-Chien Hsu (Journal of Industrial Ecology, 2026)
Tire wear particles (TWPs) constitute a significant fraction of total microplastic release, necessitating quantification for effective management. While material flow analysis (MFA) quantifies their pathways from generation to environmental sinks, existing approaches apply uniform transfer coefficients across entire regions, obscuring critical spatial heterogeneity essential for assessing ecosystem exposure. This study developed a spatially explicit, process-based MFA framework by integrating mechanistic TWP generation modeling with hydrological rainfall-runoff processes to quantify TWP generation, road surface accumulation, and storm-driven mobilization in Hong Kong. Results indicate an annual per capita TWP generation of 0.28 kg/person/year, notably lower than the global average. Over half of the generated TWPs were mobilized by stormwater runoff after road surface deposition. The hydrological transport pathway to surface water exhibits pronounced spatial and event-driven heterogeneity. Spatially, while suburban districts with extensive road networks dominated absolute emissions (24%), dense urban cores exhibited generation intensities 15 times higher and washoff intensities 18 times greater than outlying low-density areas. In terms of event dynamics, storm-event modeling demonstrates that extreme precipitation following prolonged dry periods can mobilize 30% of annual TWP loads within 24 h, fundamentally reorganizing pollution distributions. This framework provides a transferable tool for pinpointing TWP hotspots and informing targeted mitigation strategies in urban watersheds worldwide.

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

MDSN-Net: A multi-domain spectral nexus network for underwater accurate fish counting - Jiaming Xin; Tongtong Gu; Zhengmeng Wu; Yiying Wang; Dashe Li; Huanhai Yang (Computers and Electronics in Agriculture, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

A new matrix propagation method for theoretical analysis of wave propagation in low-temperature gradient layered rock mass with parallel ice-filled joints - Jiaming Wang; Zilong Zhou; Zhen Wang; Jun Hou; Ning Yang; Yaocai Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Microbial nutrient stimulation enhances in situ methanogenesis ~ 900 m depth in coalbeds: evidence from long-term field trial in Hancheng Block - Weidong Yan; Jiaming Yang; Zhidong Guo; Yingming Wang; Hui Wang; Wenhui Meng; Yang Yuan; Hailin Yang; Shoushuai Feng (Systems Microbiology and Biomanufacturing, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Aerodynamic and wake characteristic analysis of a dual-rotor wind turbine under surge motion based on modified actuator line model - Mengshang Zhao; Kai Wang; Siqi Chen; Jiaming Liu; Yuan Li (Ocean Engineering, 2026)

Ionic liquid-modulated Co/Ni heterostructure MOF nanoflower for efficient electrochemical conversion from HMF to FDCA - Shucan Qin; Weizhen Kong; Anshuang Wu; Longmei Shi; Yuhui Ci; Yunqian Ma; Na Wang; Jiaming Mao (Journal of Environmental Chemical Engineering, 2026)

A comparative study of maturity, gas emissions, and microbial communities during kitchen waste, food waste, and food waste digestate composting - Xia Gao; Jiani Wang; Jiaming Li; Kaishu Luo; Xingshuai Yang; Guoxue Li; Yilin Kong; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Structural properties of two glycans in the fruits of jujube and their regulation effect of M1-type and M2-type macrophage - Jingya Ruan; Ping Zhang; Jiaming Cheng; Lequan Yu; Yijin Wu; Yinuo Zheng; Yi Zhang; Tao Wang (Carbohydrate Polymers, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Transport modeling of ZVI-AC mixtures in Cr(VI) remediation driven by spectral induced polarization - Xinmin Ma; Alexis Maineult; Jiaming Zhang; Chen Chao; Ruijue Zhao; Jian Meng; Yaxun Wang; Deqiang Mao (Journal of Hazardous Materials, 2026)

Unintended environmental risks of regional PV expansion: A climate-adjusted lifecycle analysis for sustainable deployment - Jiawen Liu; Liangzhong Li; Yangyang Wu; Jiaming Wang; Futian Ren; Peng Wang; Lei Huang (Journal of Environmental Management, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Research on bearing capacity of laser welding reinforcement of spherical joint region of spatial grid structure - Caibao Liu; Xiongyan Li; Wei Wang; Suduo Xue; Jiaming Yang (Engineering Structures, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Anti-inflammatory metabolites from the leaves of Ohwia caudata - Qianqian Zhang; Ping Zhang; Yijin Wu; Huimin Li; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Co-pyrolysis mechanism of 1,1,1,2-tetrafluoroethane and soapstock: ReaxFF molecular dynamic and density functional theory study - Mengna Bai; Erguang Huo; Wei Zhuang; Jiaming Wang (Journal of Environmental Chemical Engineering, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Br radicals generated via bromate-free photoactivation may promote degradation of emerging contaminants in highly saline waters - Min Zhao; Jiaming Gan; Yingdong Li; Mingbao Feng; Hamid Mohammed Al-Gabr; Xin Yu; Lei Wang (Water Research, 2026)

QACO: An adaptive multi-phase ant colony optimization approach for robust feature selection - Zihang Wang; Ye Liang; Wenwei Sun; Jiaming Liu (Swarm and Evolutionary Computation, 2026)

Heterogeneous distribution of salinity and nitrogen in the root-zone influence nitrogen harvest index and natural 15N abundance of tomato - Jinjing Liu; Zhenchang Wang; Yuexiong Wang; Yaosheng Wang; Yousef Alhaj Hamoud; Cheng Hong; Hiba Shaghaleh; Rangjian Qiu; Jiaming You; Minghao Tian; Kexin Chen; Xiaoman Qiang; et al. (Plant Science, 2026)

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

Emerging evidence of nighttime mercury oxidation driven by nitrate radical-activated heterogeneous halogen chemistry - Yan Wang; Zhenya Duan; Yi Tang; Shuxiao Wang; Zhijian Li; Qin Wang; Jiaming Fu; Qingru Wu (Journal of Hazardous Materials, 2026)

Chemical constituents of Baeckea frutescens L. and their chemotaxonomic significance - Haijun Wang; Jing Wang; Chunyu Fu; Jiafeng Wang; Lei Liu; Jiaming Wang (Biochemical Systematics and Ecology, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Research on the mining pressure law of gob-side roadway under the influence of fault tectonic zones and hard roofs - Junfeng Pan; Jiting Liu; Yubing Huang; Jiaming Gao; Yucheng Wang (Bulletin of Engineering Geology and the Environment, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

High-precision mapping of aquaculture ponds based on multi-feature fusion, using Sentinel-1 and Sentinel-2 time series images - Jie Wang; Shengqi Wang; Xun Wang; Jiaming Liu (International Journal of Remote Sensing, 2025)

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Porcine liver peptide ameliorates ethanol-induced liver injury via the NQO1 and ACAA1 signaling pathway through regulating oxidative stress and lipid metabolism - Zixu Wang; Lujuan Xing; Jingyu Wang; Jiaming Cai; Yuejing Hao; Ye Tao; Wangang Zhang (Food Bioscience, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Torsional Deformation of Existing Tunnels Induced by Obliquely Undercrossing Shield Tunneling - Jiaming Ou; Xiaochun Zhong; Lisu Sun; Wei Wang (Geotechnical and Geological Engineering, 2025)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Enhancing phyto-microbial remediation of petroleum-contaminated soil using sophorolipid-modified biochar: Metagenomic and metabolomic insights - Yuhang Chen; Fumei Wang; Jiaqi Gao; Qinglong Liu; Jiaming Guo; Huan Liu (Environmental Research, 2025)

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Experimental research on mechanised strip application process based on DEM of compressed granulated straw - Guibin Chen; Jiaming Yang; Fuzeng Yang; Qingjie Wang; Zhijie Liu; Zhengdao Liu (Biosystems Engineering, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Synthesis of ultrafine boehmite from waste coal fly ash by integrating sol-gel process with sodium aluminate decomposition and hydrothermal treatment - Shuwei Lan; Zhaowen Wang; Qianhan Zhao; Zhibo Liu; Jiaming Li (Journal of Environmental Chemical Engineering, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Mechanochemical treatment and valorization of hazardous fluorine from aluminum electrolyte in spent carbon anodes - Zhibo Liu; Zhenkun He; Bingqing Liu; Wenju Tao; Jiaxin Yang; Jiaming Li; Xianwei Hu; Zhaowen Wang (Journal of Environmental Chemical Engineering, 2025)

Parallel algorithm of watershed delineation by considering the topological relationship into information organisation - Fei Zhao; Liyang Xiong; Hongen Wang; Lanhua Luo; Jiaming Na; Sijin Li; Guoan Tang (Environmental Modelling & Software, 2025)

Hybrid thermal load prediction model for the regional built environment based on random forest feature screening - Jiangxing Zhu; Tonghua Zou; Dongxia Wu; Yongchun Feng; Tianlei Wang; Jiarui Huang; Baomin Dai; Chendong Wang; Jiaming Gao (Energy and Buildings, 2025)

Br− as a potential suppressor of NDMA formation during ozonation of HDMS: Mechanisms and implications - Fan Zhou; Menglan Gao; Xiaobin Liao; Jiaming Zhu; Zhenkun Chen; Huatong Ma; Huayu Zhang; Jin Wang; Chenyang Liao; Mingzhi Huang; Zhimin Yang (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Hydrophilic and lipophilic diblock polymer-based co-delivery nanoplatform for impossible mission: Resistance management toward insecticides via Nrf2-sMaf pathway - Jiajia Zhao; Zeng Wang; Jiaming Yin; Ying Wei; Mingshan Li; Jialin Gou; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

The links between Na/K ratios in eolian sands and mean annual precipitation in the deserts of arid region, northern China - Jiaqi Wang; Shipei Dong; Zhuolun Li; Jiaming Qu; Yuhan Kuai; Dianjia Tan; Jie Luo (CATENA, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

An efficient fish counting method with adaptive global perception and multi-scale feature perception - Yiying Wang; Dashe Li; Jiaming Xin (Aquacultural Engineering, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Dynamic interplay between core functional microbial succession and flavor metabolite formation in naturally fermented sufu: A multi-omics perspective - Chen Chen; Jiaming Li; Zahoor Ahmed; Changyue Deng; Feng Wang; Jingwei Hu; Yibin Zhou (Food Bioscience, 2025)

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

Calibration is required for use of electromagnetic soil moisture sensors to accurately measure the water content of tree stems and sawdust - Jiaming Wang; Neil C. Turner; Hailong He (Plant and Soil, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Study on membrane electrolysis for the removal of Fe from the leachate of coal fly ash - Shuwei Lan; Youjian Yang; Zhaowen Wang; Yanchen Zheng; Jiaming Li; Qianhan Zhao; Tingting Liu (Journal of Environmental Chemical Engineering, 2025)

Dynamic optimization of cooling temperature setpoints in multiple thermal zones of office buildings in connection with D3QN - Ben Jiang; Jiaming Wang; Yu Li; Peng Wang; Yacine Rezgui; Chengyu Zhang; Menglin Ding; Liuyang Shangguan; Tianyi Zhao (Energy and Buildings, 2025)

Emission Characteristics and Absorption Removal of Ultra-high Concentration NOx in an Arc-Heated Wind Tunnel - Zhiliang Xue; Jie Yuan; Jiaming Shao; Pei Li; Yonggang Zhou; Tao Zhu; Zhihua Wang (International Journal of Environmental Research, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Better inversion of rice nitrogen nutrition index at early panicle initiation stage using spectral features, texture features, and wavelet features based on UAV multispectral imagery - Ziwei Li; Yuliang Zhang; Jiaming Lu; Yuan Wang; Can Zhao; Weiling Wang; Jianjun Wang; Hongcheng Zhang; Zhongyang Huo (European Journal of Agronomy, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

A deep learning-based data augmentation method for marine mammal call signals - Jiaming Jiang; Wanlu Cheng; Shengwen Gong; Jingjing Wang (Frontiers in Marine Science, 2025)
In marine ecology research, it is crucial to accurately identify the marine mammal species active in the target area during the current season, which helps researchers understand the behavioral patterns of different species and their ecological environment. However, the difficulty and high cost of collecting marine mammal calls, coupled with limited publicly available datasets, result in insufficient data for support, making it difficult to obtain accurate and reliable identification results. To address this problem, we propose MarGEN, a deep learning-based augmentation method for marine mammal call signal data. This method processed the call data into Mel spectrograms, then designed a self-attention conditional generative adversarial network to generate new samples of Mel spectrograms that were highly similar to the real data, and finally reconstructed them into call signals using WaveGlow. The classification experiments on the calls of four Marine mammals show that MarGEN significantly enriches the diversity and volume of the data, increasing the classification accuracy of the model by an average of 4.7%. The method proposed in this paper greatly promotes marine ecological protection and sustainable development, while effectively advancing research progress in bionic covert underwater acoustic communication technology.

Efficient and anti-interference plastic classification method suitable for one-shot learning based on laser induced breakdown spectroscopy - Zhiying Xu; Xingyu Zhao; Xinying Peng; Kai Wang; Kedong Wang; Nan Zhao; Jiaming Li; Qingmao Zhang; Xueqing Yan; Kun Zhu (Chemosphere, 2025)

Global-scale gap filling of satellite soil moisture products: Methods and validation - Chunlin Zhang; Jiangyuan Zeng; Pengfei Shi; Hongliang Ma; Husi Letu; Xiang Zhang; Panshan Wang; Haiyun Bi; Jiaming Rong (Journal of Hydrology, 2025)

Ultrasensitive nanoenzymes-based lateral flow immunoassay platform for accurate detection of folic acid in human serum - Jinbo Cao; Tiemei Li; Xianglin Liao; Jiaming Zhang; Xixiang Yang; Huiqi Yan; Boyang Sun; Yanfei Li; Jiaxiang Huang; Yao Wang; Xiaogang Hu; Li Wang (Chemical Engineering Journal, 2025)

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Sensor fault diagnosis and calibration based on voting mechanism for online application using virtual in-situ calibration and time series prediction - Jiteng Li; Jiaming Wang; Peng Wang; Sungmin Yoon; Yu Li; Yacine Rezgui; Yuxin Li; Tianyi Zhao (Building and Environment, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Spatial-temporal evolution of landslides spanning the impoundment of Baihetan mega hydropower project revealed by satellite radar interferometry - Jiaming Yao; Teng Wang; Xin Yao (Remote Sensing of Environment, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Efficient lithium recycling from waste aluminum electrolytes through an environmentally friendly process - Jiaxin Yang; Wenju Tao; Jiaming Li; Jingui He; Zhaowen Wang (Chemical Engineering Journal, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Low-dose exposure to microplastics retards meiotic maturation via HDAC3 insufficiency - Qi Zhao; Ming Zong; Entong Song; Hongye Linghu; Xuanwen Li; Baicui Wang; Songling Xiao; Wanchun Guan; Jianzhong Su; Jiaming Zhang; Jingzhang Ji; Qingran Kong (Science China Life Sciences, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

Application of cryogenic grinding combined with ultrasonic pretreatment to enhance the yield and quality of essential oils from nutmeg (Myristica fragrans Houtt.) - Jiaming Yan; Sidan Zhao; Zhengyun Liang; Hanchen Lin; Ning Ma; Chaoqun You; Fei Wang (Sustainable Chemistry and Pharmacy, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Genome-wide identification of the SmPHR gene family in Salvia miltiorrhiza and SmPHR7-mediated response to phosphate starvation in Arabidopsis thaliana - Xinxin Wang; Renjun Qu; Shiwei Wang; Jiaming Peng; Juan Guo; Guanghong Cui; Tong Chen; Meilan Chen; Ye Shen (Plant Cell Reports, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

Interaction between imidacloprid residues in maize rhizospheric soil and soil nematode community - Jiaming Zhang; Yue Wu; Jiayi Liu; Xinru Wang; Weijia Pang; Juan Hua; Shihong Luo (Pesticide Biochemistry and Physiology, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Chronic chlorpyrifos exposure induces oxidative stress, neurological damage, and hepatopancreas enrichment in Chinese mitten crab (Eriocheir sinensis) - Yuanyuan Tan; Jiaming Dong; Luyao Wang; Weining Li; Jie Bao; Hongbo Jiang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Preparation of a smart nano-herbicide MP@HLDP with strong permeability performance improves herbicidal activity while reducing the adverse impacts - Xile Deng; Zeng Wang; Jiaming Yin; Zhichao Dong; Jie Shen; Shuo Yan; Lianyang Bai (Chemical Engineering Journal, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Overcoming carbon deposition in non-thermal plasma catalyzed biomass tar reforming: Innovative strategies employed by GPPC systems - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Yiqiang Liu; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Guilin Piao (Fuel, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Safety control of blasting vibration in new tunnel excavation adjacent to existing tunnel - Junru Zhang; Zhijian Yan; Jianchi Ma; Qihua Deng; Jiaming Liu; Jimeng Feng; Zhiyong Wang (Bulletin of Engineering Geology and the Environment, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Excessive nitrogen application reduces eating quality by changing the starch molecular structure and physicochemical properties of inferior grains - Can Zhao; Yue Chen; Kunlun Liu; Guangming Liu; Jiaming Lu; Weiling Wang; Zhongyang Huo (Journal of Cereal Science, 2025)

Enhanced steam reforming of benzene in a two-stage catalytic system: Insights into metal synergies and carbon deposition evolution - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Yuan Sun (Fuel, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Haversian bone mimicking scaffold with built-in vasculature for bone tissue engineering - Jian Liu; Zhen You; Xinmei Li; Boyang Zhang; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

Development of poly(butylene oxalate-co-furanoate) copolymers with enhanced sustainability and hydrolytic degradability - Lizheng Wang; Zhu Tu; Jiaming Liang; Yanyu Wang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

The energy system transition pathway towards carbon reduction using a model-coupling approach - Jiali Zheng; Xiaoqing Hou; Jiaming Yang; Lianyang Jiao; D’Maris Coffman; Shouyang Wang (Global Environmental Change, 2024)

Study on strength and reduction characteristics of iron ore powder-green carbon composite briquettes - Yifan Chai; Shijie Wang; Jiaming Zhang; Yanshuo Shi; Peijun Liu; Shengli An; Chuan Wang; Xiaojun Ning (Fuel, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

Lotus rhizome-inspired superhydrophobic capillarity mesh surface for long-term plastron stability - Jiaming Wang; Yuhong Liu (Chemical Engineering Journal, 2024)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Nano ZnO modified amorphous carbon materials enabling long-cycle performance and high-capacity for lithium/sodium-ion batteries - Jiaming Liu; Zhen He; Tongfa Zhao; Yuqian Wei; lingpei Hou; Yunfei Song; Yuxin Wang (Chemical Engineering Journal, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Trajectory tracking PID passivity-based control of spacecraft formation flying around Sun-Earth L2 point in the port-Hamiltonian framework - Jiaming Wang; Qingrui Zhou; Wei Zheng; Jingdong Diao (Advances in Space Research, 2024)

Carbonate system in the subtropical Jiulong River Estuary and CO2 flux estimation under modulation of tidal cycle - Weicong Chen; Heng Sun; Zhongyong Gao; Jiaming Lin; Min Xu; Aijun Wang; Shuqin Tao (Acta Oceanologica Sinica, 2024)

Online sorting of surface defective walnuts based on deep learning - Jingwei Wang; Xiaopeng Bai; Daochun Xu; Wenbin Li; Siyuan Tong; Jiaming Zhang (Journal of Food Engineering, 2024)

A novel process for recovering LNCM battery cathode material using cryolite-based electrolyte through selective dissolution - Acid leaching - Coprecipitation - Jiaming Li; Youjian Yang; Jiaxin Yang; Shuwei Lan; Zhaowen Wang (Journal of Cleaner Production, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Recent research progress of MOFs-based heterostructures for photocatalytic hydrogen evolution - Jiaming Li; Jia Jia; Deping Wang; Hongjun Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Southwest Boundary of Yangtze and Cathaysia Blocks: Constraints from the Luojiashan Gabbro in Yingyangguan Region, Northeastern Guangxi - Ya Qin; Zuohai Feng; Jiaming Zhu; Yonggao Huang; Jie Wu; Yun Zhou; Yunfeng Xue; Chunzeng Wang (Journal of Earth Science, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

A novel intelligent indoor fire and combustibles detection method based on multi-channel transfer learning strategy with acoustic signals - Zhihua Wang; Zipeng Zhang; Zhuoyue Wang; Jiaming Lu; Weiguang An (Process Safety and Environmental Protection, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

Assessing geological hazard susceptibility and impacts of climate factors in the eastern Himalayan syntaxis region - Jiaming Yao; Yanbing Wang; Teng Wang; Beibei Zhang; Yuming Wu; Xin Yao; Zheng Zhao; Shu Zhu (Landslides, 2024)

Facet-dependent activation of oxalic acid over hematite nanocrystals under the irradiation of visible light for efficient degradation of pollutants - Zhixiong Yang; Yuan Li; Xiaotian Wang; Jiaming Li; Jiquan Wang; Gaoke Zhang (Journal of Environmental Sciences, 2024)

Boosting charge transfer promotes photocatalytic peroxymonosulfate activation of S-doped CuBi2O4 nanorods for ciprofloxacin degradation: Key role of Ov–Cu–S and mechanism insight - Xianzhong Bu; Jiaming Li; Jin Wang; Yuan Li; Gaoke Zhang (Chemical Engineering Journal, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Joint optimal allocation of regional water and land resources considering their mutual feed relationship - Chengguo Su; Zhenglei Hu; Wenlin Yuan; Jiaming Zhang; Denghua Yan; Huiliang Wang (Journal of Hydrology, 2024)

Contributions of China's terrestrial ecosystem carbon uptakes to offsetting CO2 emissions under different scenarios over 2001–2060 - Mengyang Xu; Ziyu Zhang; Chao Yue; Jie Zhao; Pengyi Zhang; Mengyu Wang; Jiaming Wang; Hongfei Zhao; Jinyue Liu; Xianhui Tang; Junhao He (Global and Planetary Change, 2024)

Effects and mechanisms of ultrasound-assisted emulsification treatment on the curcumin delivery and digestive properties of myofibrillar protein-carboxymethyl cellulose complex emulsion gel - Lei Zhou; Jiaming Cai; Jingyu Wang; Chao Ma; Lujuan Xing; Siah Ying Tang; Wangang Zhang (Food Research International, 2024)

Development of a water gradient film through film and ice-glazing approach utilizing konjac glucomannan and high acyl gellan gum for enhanced preservation of frozen snakehead (Channa argus) fillets - Man Xiao; Chun Peng; Jiaming Qin; Shuangshuang Wang; Xiaohe Wu; Katsuyoshi Nishinari; Fatang Jiang (Food Hydrocolloids, 2024)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

Stepwise extraction of lithium and potassium and recovery of fluoride from aluminum electrolyte wastes through calcification roasting–two-stage leaching - Shaohua Wu; Wenju Tao; Hui Ge; Jiaxin Yang; Jiaming Li; Jingui He; Youjian Yang; Zhaowen Wang (Environmental Science and Pollution Research, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Orbital forcing of aridity/humidity fluctuations in the Hexi Corridor and Alxa Plateau, NW China, during the last 1.8 million years - Dianbao Chen; Jiaming Yang; Junsheng Nie; Fei Wang; Qinhong Mo; Baotian Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Poly(butylene oxalate-co-terephthalate): A PBAT-like but rapid hydrolytic degradation plastic - Lizheng Wang; Zhu Tu; Jiaming Liang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Identification of toll-like receptor family and the immune function of new Sptlr-6 gene of Scylla paramamosain - Bohao Peng; Jiaming Lin; Haifu Wan; Pengfei Zou; Ziping Zhang; Yilei Wang (Fish & Shellfish Immunology, 2024)

Effects of polymerization types on plastics ingestion and biodegradation by Zophobas atratus larvae, and successions of both gut bacterial and fungal microbiomes - Yue Weng; Xiaoyu Han; Huayang Sun; Jiaming Wang; Yumeng Wang; Xin Zhao (Environmental Research, 2024)

Applicability and limitation of compost maturity evaluation indicators: A review - Yilin Kong; Jing Zhang; Xuanshuo Zhang; Xia Gao; Jie Yin; Guoying Wang; Jiaming Li; Guoxue Li; Zhongliang Cui; Jing Yuan (Chemical Engineering Journal, 2024)

Rab18 maintains homeostasis of subcutaneous adipose tissue to prevent obesity-induced metabolic disorders - Jiaming Liu; Liangkui Li; Dijin Xu; Yuqi Li; Tao Chen; Yeyang Liu; Yuqian Bao; Yan Wang; Longyan Yang; Peng Li; Li Xu (Science China Life Sciences, 2024)

Comparative study on dynamic responses of integrated installation process of a 5-MW and a 15-MW offshore wind turbine considering a pre-installed foundation - Jiaming Liu; Zhongming Xiao; Kai Wang; Shuo Huang; Yu Du (Ocean Engineering, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

Biochanin a ameliorates DSS-induced ulcerative colitis by improving colonic barrier function and protects against the development of spontaneous colitis in the Muc2 deficient mice - Haina Zhang; Xueqi Wang; Linxian Zhao; Kai Zhang; Jiaming Cui; Guangmeng Xu (Chemico-Biological Interactions, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Development of a 3D point cloud reconstruction-based apple canopy liquid sedimentation model - Chongchong Chen; Yalan Jia; Jiaming Zhang; Linsen Yang; Yaxiong Wang; Feng Kang (Journal of Cleaner Production, 2024)

Polystyrene microplastics with absorbed nonylphenol induce intestinal dysfunction in human Caco-2 cells - Fangfang Ding; Huimei Wang; Yingzhi Li; Xueping Leng; Jiaming Gao; Danfei Huang (Environmental Toxicology and Pharmacology, 2024)

The relationship between repeated impacts and CAI strength of sandwich structure considering different impactor shape in individual impact - Keyu Zhu; Xitao Zheng; Jiaming Sun; Guoyue Wang; Leilei Yan (Engineering Structures, 2024)

Hyporheic exchange in a compound channel under unsteady flow: Numerical simulations - Jiaming Liu; Yang Xiao; Pei Xin; Nairu Wang; Saiyu Yuan; Taotao Zhang; Chentao Li; Carlo Gualtieri (Journal of Hydrology, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

Effects of ultrasound-assisted emulsification and carboxymethyl cellulose addition on the rheological and microstructure properties of myofibrillar protein-soybean oil emulsion gel - Lei Zhou; Dacheng Kang; Jingyu Wang; Jiaming Cai; Lujuan Xing; Wangang Zhang (Food and Bioproducts Processing, 2024)

Zinc saponite protection layer with fast zinc-ion transfer kinetics to enable highly reversible Zn anode - Jiaming Li; Hanhao Liang; Jian Wu; Jiancheng Xu; Yini Long; Jianglin Wang; Zhanhong Yang (Chemical Engineering Journal, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Distribution patterns and influential factors of pathogenic bacteria in freshwater aquaculture sediments - Wenxiang Xi; Xun Zhang; Xianbin Zhu; Jiaming Wang; Han Xue; Hongzhong Pan (Environmental Science and Pollution Research, 2024)

FRPNet: An improved Faster-ResNet with PASPP for real-time semantic segmentation in the unstructured field scene - Biao Yang; Sen Yang; Peng Wang; Hai Wang; Jiaming Jiang; Rongrong Ni; Changchun Yang (Computers and Electronics in Agriculture, 2024)

Minor chromium passivation of S-ZVI enhanced the long-term dechlorination performance of trichlorethylene: Effects of corrosion and passivation on the reactivity and selectivity - Jiaming Guo; Dong Wang; Yinghao Shi; Honghong Lyu; Jingchun Tang (Water Research, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Effectively solve the obstacle in the old residential building energy-saving renovation from the perspective of a four-party evolutionary game - Peng Wang; Haiyun Chen; Zhiyuan Si; Ling Jia; Jiaming Wang; Keying Li; Chenglong Wang (Environmental Science and Pollution Research, 2024)

Taurochenodeoxycholic acid exerts anti-viral activities upon SGIV infection via anti-inflammatory response - Fengyi Zhu; Weihua Xu; Wenji Wang; Jiaming Liao; Youhua Huang; Xiaohong Huang; Qiwei Qin (Aquaculture, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Rheological and tribological properties of high internal phase emulsions stabilized by pH-induced soy protein isolate-carrageenan complex coacervates - Fanjun Meng; Jiaming Li; Cong Yang; Miao Wang; Xiao Liu (Food Hydrocolloids, 2024)

Using geodetic measurements derived terrestrial water storage to investigate the characteristics of drought in Yunnan, China - Chao Chen; Rong Zou; Zhiwei Fang; Jiaming Cao; Qi Wang (GPS Solutions, 2024)
The use of the global navigation satellite system (GNSS) for monitoring changes in terrestrial water storage (TWS) is growing. However, the density of GNSS stations is sparse in most areas, and the widely used Green’s function (GF) method cannot provide a satisfactory resolution for inversion problems. As the Slepian basis function (SBF) method has been successfully used for gravity inversions, GNSS geodesists have recently applied the SBF method to GNSS displacements. However, the evaluation of TWS differences inferred from GNSS using the SBF and the GF has been rarely assessed. In this study, we use both the GF and the SBF methods to investigate the TWS in Yunnan by using more than ten years (2010–2021) of GNSS observations. We observe a remarkable consistency between the two inversion methods employed for GNSS data, as well as a strong agreement with equivalent water heights (EWH) inferred from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GFO), hydrological model (GLDAS-NOAH), and precipitation data, despite variations in the amplitude. Furthermore, affected by monsoon climate and topography, Yunnan is prone to drought. We analyze the main nine drought events, evaluate the connection between GNSS-inverted TWS during 2010–2021, and find that almost all droughts in Yunnan occurred during the "trough period" within the GNSS-DSI.

An image-based system for locating pruning points in apple trees using instance segmentation and RGB-D images - Siyuan Tong; Jiaming Zhang; Wenbin Li; Yaxiong Wang; Feng Kang (Biosystems Engineering, 2023)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

In-situ preparation of N-rich nano-activated carbon on negative-charged montmorillonite with enhanced activation of peroxymonosulfate for antibiotics degradation - Wei Wang; Yan Huang; Jiaming Ni; Weijun Peng; Yijun Cao; Yukun Huang; Guixia Fan; Daoguang Teng; Shaoxian Song (Journal of Environmental Chemical Engineering, 2023)

Recent advances in nanomaterial-enhanced persulfate activation for organic pollutants removal: Electron transfer, surface reactions, and radical generation - Dingren Ma; Ji Mei; Qiwen Liang; Yimu Jiao; Tianyu Hu; Jingchen Chen; Jiaming Wang; Hao Zhou; Qiyu Lian; Mingzhe Sun; Dehua Xia; Tianqi Wang (Journal of Environmental Chemical Engineering, 2023)

Investigation of Mechanical Properties of Quartz and Illite in Shale Using Molecular Dynamics Simulation - Shuang Liang; Mingyu Gao; Shuo Sun; Yikun Liu; Wanxin Li; Jingkun Wang; Jiaming Wang; Chengfeng Yin (Natural Resources Research, 2023)

Catalytic ozonation of multi-VOCs mixtures over Cr-based bimetallic oxides catalysts from simulated flue gas: Effects of NO/SO2/H2O - Peixi Liu; Hairong Tang; Jiaming Shao; Yong He; Yanqun Zhu; Elisabete C.B.A. Alegria; Zhihua Wang; Armando J.L. Pombeiro (Chemosphere, 2023)

Revealing the spatio-temporal characteristics and impact mechanism of carbon emission in China's urban agglomerations - Ziyi Wang; Jingxiang Zhang; Pingjia Luo; Dongqi Sun; Jiaming Li (Urban Climate, 2023)

Analysis of variation characteristics, transport paths, and influencing factors of atmospheric NO2 pollution in Western Europe - Jiaming Zhang; Tianzhen Ju; Bingnan Li; Chunxue Li; Jinyang Wang; Xuhui Xia; Xiaowen Niu (Environmental Monitoring and Assessment, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Abundance, characteristics and seasonal variation of microplastics in a domestic sewage treatment plant in Nanjing, China - Juan Huang; Jing Tuo; Luming Wang; Jiaming Liu (Journal of Water Process Engineering, 2023)

Biological treatment as a green approach for enhancing electrochemical performance of wood derived carbon based supercapacitor electrodes - Jiaming Cao; Lin Lin; Jian Zhang; Feng Zhao; Junyou Shi; Fachun Guan; Dongliang Wang (Journal of Cleaner Production, 2023)

Ingestion preference and efficiencies of different polymerization types foam plastics by Tenebrio molitor larvae, associated with changes of both core gut bacterial and fungal microbiomes - Yijing Wang; Xin Zhao; Jiaming Wang; Yue Weng; Yumeng Wang; Xin Li; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2023)

Identification of hepatoprotective peptides from porcine liver and its interaction with ethanol metabolizing enzymes in vitro - Zixu Wang; Lujuan Xing; Jiaming Cai; Fidel Toldrá; Yuejing Hao; Wangang Zhang (Food Bioscience, 2023)

Extreme low-temperature events can alleviate micronutrient deficiencies while increasing potential health risks from heavy metals in rice - Min Kang; Xue Wang; Jiankun Chen; Qizhao Fang; Jiaming Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu; Bing Liu (Environmental Pollution, 2023)

Experimental study on the characteristics of radiation floor cooling system based on an earth–air heat exchanger - Jiaming Yang; Wei Song; Houan Zhang; Jing Wang; Jiankai Dong (Energy and Buildings, 2023)

Spatial and temporal distribution of absorbing aerosols in sub-Saharan Africa and GTWR model analysis - Chunxue Li; Tianzhen Ju; Bingnan Li; Jiaming Zhang; Jinyang Wang; Xuhui Xia; Shengtong Lei (Air Quality, Atmosphere & Health, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Development of geopolymer-based composites for geothermal energy applications - Linfeng Zhang; Yingfan Wang; Boyin Ding; Jiaming Gu; Neven Ukrainczyk; Jingming Cai (Journal of Cleaner Production, 2023)

Engaging stakeholders in collaborative control of air pollution: A tripartite evolutionary game of enterprises, public and government - Jiaming Wang; Ling Jia; Pan He; Peng Wang; Lei Huang (Journal of Cleaner Production, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

An interval-valued carbon price forecasting method based on web search data and social media sentiment - Jinpei Liu; Xue Li; Piao Wang; Huayou Chen; Jiaming Zhu (Environmental Science and Pollution Research, 2023)

Degradation and dechlorination of trichloroacetic acid induced by an in situ 222 nm KrCl* excimer radiation - Jiaming Gan; Ting Zhu; Yizhan Zhang; Dailin Li; Ting Li; Min Zhao; ZengXia Zhao; Lei Wang (Chemosphere, 2023)

Abundance, characteristics, and removal of microplastics in different wastewater treatment plants in a Yangtze River Delta city of China - Juan Huang; Luming Wang; Jiaming Liu; Xiuwen Qian; Yufeng Wu (Journal of Water Process Engineering, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

Enhancement of sodium salty taste modulate by protease-hydrolyzed Gum Arabic - Kailin Ye; Jiaming Qi; Yang Zhang; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2023)

Analysis on the Influencing Factors and Future Trend of HCHO Pollution in Brazil - Cheng Huang; Tianzhen Ju; Bingnan Li; Jinyang Wang; Jiaming Zhang; Shengtong Lei; Chunxue Li (Water, Air, & Soil Pollution, 2023)

A Real-Time Lightweight Detection Algorithm for Deck Crew and the Use of Fishing Nets Based on Improved YOLOv5s Network - Jiaming Wang; Xiangbo Yin; Guodong Li (Fishes, 2023)
A real-time monitoring system for the operational status of fishing vessels is an essential element for the modernization of the fishing industry. The operational status of fishing vessels can be identified by using onboard cameras to detect the deck crew and the use of fishing nets. Due to the typically limited processing capacity of shipboard equipment and the significant memory consumption of detection models, general target detection models are unable to perform real-time image detection to identify the operational status of fishing vessels. In this paper, we propose a lightweight real-time deck crew and the use of a fishing net detection method, YOLOv5s-SGC. It is based on the YOLOv5s model, which uses surveillance cameras to obtain video of fishing vessels operating at sea and enhances the dataset. YOLOv5s-SGC replaces the backbone of YOLOv5s with ShuffleNetV2, replaces the feature fusion network with a modified Generalized-FPN, and adds the CBAM attention module in front of the detection head.

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Self-powered health monitoring with ultrafast response and recovery enabled by nanostructured silicon moisture-electric generator - Yuhang Song; Chang Shu; Zheheng Song; Xuelian Zeng; Xianrong Yuan; Yanan Wang; Jiaming Xu; Qianyue Feng; Tao Song; Beibei Shao; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2023)

Magnetic field assisted process for preparing anti-biofouling PVDF membranes incorporated by hydrophilic magnetic palygorskite - Hengyang Mao; Jiayun Zhu; Shouyong Zhou; Jiaming Wang; Mengting Li; Ailian Xue; Meisheng Li; Yijiang Zhao; Wenbo Peng; Weihong Xing (Applied Clay Science, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

FOXO-like Gene Is Involved in the Regulation of 20E Pathway through mTOR in Eriocheir sinensis - Jiaming Li; Yuhan Ma; Zhichao Yang; Fengchi Wang; Jialin Li; Yusheng Jiang; Dazuo Yang; Qilin Yi; Shu Huang (Journal of Marine Science and Engineering, 2023)
The Forkhead Box O (FOXO) gene plays a key role in various biological processes, such as growth, metabolism, development, immunity and longevity. Molting is an essential process for crustacean growth, which is mainly regulated by 20-hydroxyecdysone (20E) and molt-inhibiting hormone (MIH). Although the role of FOXO in regulating the immune response of crustaceans is well documented, its involvement in controlling crustacean molting remains unclear. In this study, a FOXO-like gene (designed as EsFOXO-like) was identified in Eriocheir sinensis, and the regulation of the 20E pathway by EsFOXO-like was also investigated. The coding sequence of EsFOXO-like was 852 bp, which consisted of 283 amino acids including a conserved Forkhead (FH) domain. EsFOXO-like shared high similarity with FOXO genes from other crustaceans, and the mRNA expression levels of the EsFOXO-like gene were highest in the hepatopancreas and lowest in the hemocytes. However, transcription and protein expression of the EsFOXO-like gene were found to be up-regulated only during the pre-molt stage in the hepatopancreas, with lower expression levels observed at the post-molt stage. To explore the role of EsFOXO-like in the 20E pathway, EsFOXO-like was firstly inhibited by a specific FOXO inhibitor (AS1842856) and then through an EsFOXO-like dsRNA injection, respectively, and the results showed that the relative expression levels of EsFOXO-like were notably decreased in the hepatopancreas after both the inhibitor and dsRNA treatments. The 20E concentration, the mRNA expression levels of the 20E receptors including the ecdysone receptor (EcR) and the retinoid-X receptor (RXR) and EsmTOR transcription in the AS1842856 group or the EsFOXO-RNAi group were all significantly higher than that in the control group, while the mRNA expression level of EsMIH was significantly decreased after EsFOXO-like inhibition. To further investigate whether the EsFOXO-like acts through mTOR or not, Rapamycin was administered to inhibit mTOR activity in EsFOXO-like inhibited crabs. The results revealed a significant reduction in the concentration of 20E and the expression level of EsMIH in the AS1842856 + Rapamycin group compared to the AS1842856 + DMSO group, accompanied by an increase in EsEcR and EsRXR expression. These findings collectively suggest that EsFOXO-like regulates the 20E pathway through mTOR, which offered valuable insights into the understanding of the molting process in crustaceans.

The heterogeneity impact of factor market distortions on GTFP: from the view of resource-based cities - Jiaming Wang; Lianyong Feng; Bo Li (Environmental Science and Pollution Research, 2023)

Observation of black carbon in Northern China in winter of 2018–2020 and its implications for black carbon mitigation - Yang Wang; Qiuge Ju; Zhenyu Xing; Jiaming Zhao; Song Guo; Fuxing Li; Ke Du (Science of The Total Environment, 2023)

Why the same economic reform leads to different urbanization route? --The comparative study of China and India - Jiaming Li; Ziyi Wang; Mingyi Liu (Land Use Policy, 2023)

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

Effects of operating conditions on supercritical methanol liquefaction of polypropylene - Binbin Fu; Litao Geng; Guangchao Jia; Zhilong Yuan; Peitao Zhao; Rongyang Zhao; Cuiping Wang; Jiaming Li (Journal of Environmental Chemical Engineering, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion - Lei Zhou; Jinyuan Jiang; Fan Feng; Jingyu Wang; Jiaming Cai; Lujuan Xing; Guanghong Zhou; Wangang Zhang (Carbohydrate Polymers, 2023)

The role of the joint capsule in the stability of the elbow joint - Fang Wang; Hao Wang; Mingxin Li; Shuoqi Jia; Jiaming Wang; Jianguo Zhang; Yubo Fan (Medical & Biological Engineering & Computing, 2023)

Assessment of Regional Differences in the Implementation of the Air Pollution Prevention and Control Action Plan in China - Yahan Gu; Yangyang Wu; Jiaming Wang; Lei Huang (Bulletin of Environmental Contamination and Toxicology, 2023)

MLKL and other necroptosis-related genes promote the tumor immune cell infiltration, guiding for the administration of immunotherapy in bladder urothelial carcinoma - Boqiang Zhong; Youzhi Wang; Yihao Liao; Jiaming Liang; Keke Wang; Diansheng Zhou; Yang Zhao; Ning Jiang (Apoptosis, 2023)
The involvement of necroptosis in the immunosuppressive tumor microenvironment has been established and has been shown to contribute to the growth of pancreatic ductal adenocarcinoma, indicating its role in promoting tumor development. However, the relationship between necroptosis and bladder urothelial carcinoma (BUC) has yet to be fully understood. To shed light on this issue, our study aimed to uncover the impact of necroptosis on immune cell infiltration and immunotherapy response in BUC patients. We conducted an analysis of 67 necroptosis genes to assess their expression and genomic changes across pan-cancer and identified 12 necroptosis genes that are prognostically relevant and associated with immune subtypes and tumor stemness in BUC. Using a public database of 1841 BUC samples, we then performed Unsupervised Cluster Analysis and discovered two distinct necroptotic phenotypes in BUC. These phenotypes showed significant differences in molecular subtypes, immune infiltration patterns, and gene mutation profiles. We confirmed this discovery in BUC through qPCR and WB experiments. To evaluate the impact of necroptosis on prognosis, chemotherapy sensitivity, and immunotherapy response (such as anti-PD-L1), we developed a principal component analysis model called NecroScore. Finally, we validated the effects of RIPK3 and MLKL through a nude mouse transplantation model for BUC. Our study has uncovered that necroptosis plays a role in shaping the tumor immune microenvironment in BUC. The high necroptosis phenotype (Cluster B) was characterized by a higher abundance of tumor immunosuppressive cells and more key biological processes driving tumor progression, while the low necroptosis group (Cluster A) had higher FGFR3 mutations. We found that the infiltration levels of immune cells, including CD8+ T cells, were significantly different between FGFR3 mutated and wild-type (WT) samples. Our results confirmed the reliability of NecroScore as a comprehensive assessment tool for evaluating the immunotherapeutic effect and prognosis of BUC patients, with high NecroScore values favoring basal-like differentiation and lower FGFR3 alterations. We also observed that high expression of MLKL had a significant inhibitory effect on tumor growth and increased neutrophil infiltration in vivo. In our study, we uncovered the regulation pattern of necroptosis in the tumor immune microenvironment of BUC. Additionally, we developed a scoring tool called NecroScore that can be utilized to predict the most suitable chemotherapy and immunotherapy strategy for bladder urothelial carcinoma patients. This tool can effectively guide the chemotherapy and immunotherapy regimens for patients with advanced BUC.

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Global-aware siamese network for change detection on remote sensing images - Ruiqian Zhang; Hanchao Zhang; Xiaogang Ning; Xiao Huang; Jiaming Wang; Wei Cui (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Preparation of a novel metal-free polypyrrole-red phosphorus adsorbent for efficient removal of Cr(VI) from aqueous solution - Longyu Qiu; Yingjun Wang; Rui Sui; Chenxi Zhu; Weiwei Yang; Yongsheng Yu; Jiaming Li (Environmental Research, 2023)

Hollow 1D carbon tube core anchored in Co3O4@SnS2 multiple shells for constructing binder-free electrodes of flexible supercapacitors - Jiaming Wang; Ying Huang; Xianping Du; Shuai Zhang; Meng Zong (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Genomic Profiling of Lower-Grade Gliomas Subtype with Distinct Molecular and Clinicopathologic Characteristics via Altered DNA-Damage Repair Features - Aierpati Maimaiti; Yanwen Liu; Aimitaji Abulaiti; Xixian Wang; Zhaohai Feng; Jiaming Wang; Maimaitili Mijiti; Mirzat Turhon; Nilipaer Alimu; Yongxin Wang; Wenbao Liang; Lei Jiang; et al. (Journal of Molecular Neuroscience, 2023)

Experimental investigation on pressure oscillation induced by steam injection into subcooled water through an opposite nozzle - Haitao Ren; Dingding Liang; Tao Lu; Jie Wang; Pei Yu; Jie Li; Jiaming Zhao; Ping Xiong (Annals of Nuclear Energy, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Antibacterial anodic aluminium oxide-copper coatings on aluminium alloys: preparation and long-term antibacterial performance - Jiahuan Chen; Zhen He; Jiaming Liu; Yuxin Wang; Michael Hodgson; Wei Gao (Chemical Engineering Journal, 2023)

miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Analysis of droplet deposition and maize (Zea mays L.) growth control: Application of ethephon by small unmanned aerial vehicle and electric knapsack sprayer - Zhao Wang; Mujahid Hussain; Jiaming Yin; Mengying Yuan; You Mo; Mengping Quan; Liusheng Duan; Weiming Tan (Field Crops Research, 2023)

Effect of Se application on selenium accumulation and fruit quality in pear (Pyrus ussuriensis) - Chi Yuan; Haidong Bu; Jiaming Zhao; Jiaojiao Liu; Guobao Wang; Hui Yuan; Aide Wang (Acta Physiologiae Plantarum, 2023)

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

Biological hydrogen with industrial potential: Improvement and prospection in biohydrogen production - Weixian Chen; Tianpei Li; Yangyi Ren; Jiaming Wang; Hui Chen; Qiang Wang (Journal of Cleaner Production, 2023)

Spatiotemporal patterns of fire-driven forest mortality in China - Jie Zhao; Jiaming Wang; Yifan Meng; Ziqiang Du; Hui Ma; Linghua Qiu; Qi Tian; Liang Wang; Mengyang Xu; Hongfei Zhao; Chao Yue (Forest Ecology and Management, 2023)

Improved catalytic activity and stability of Cu/ZnO catalyst by boron oxide modification for low-temperature methanol synthesis - Fei Chen; Jiaming Liang; Fan Wang; Xiaoyu Guo; Weizhe Gao; Yasuharu Kugue; Yingluo He; Guohui Yang; Prasert Reubroycharoen; Tharapong Vitidsant; Noritatsu Tsubaki (Chemical Engineering Journal, 2023)

Design, synthesis, and biological evaluation of dual-target COX-2/5-LOX inhibitors for the treatment of inflammation - Le Du; Shuaishuai Du; Jiaming Li; Hongwei Wang (Medicinal Chemistry Research, 2023)

Effects of leaf scorch on chlorophyll fluorescence characteristics of walnut leaves - ChangJie Xing; ShiWei Wang; CuiFang Zhang; Tong Guo; HongLong Hao; ZhuoYa Zhang; Sheng Wang; JiaMing Shu (Journal of Plant Diseases and Protection, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

A sustainable development pattern integrating data centers and pasture-based agrivoltaic systems for ecologically fragile areas - Jiaming Zhang; Tao Wang; Yuan Chang; Bingsheng Liu (Resources, Conservation and Recycling, 2023)

Effects of arsenic–iron–dissolved organic matter interactions on arsenic mobilization: Insight from column experiments - Ziyi Xiao; Xianjun Xie; Kunfu Pi; Jiaming Gong; Yanxin Wang (Journal of Hydrology, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Fracture behavior investigation of self-compacting rubberized concrete by DIC and mesoscale modeling - Xing Li; Fuheng Ma; Xudong Chen; Jiang Hu; Jiaming Wang (Journal of Cleaner Production, 2023)

Analysis and intervention of heatwave related economic loss: Comprehensive insights from supply, demand, and public expenditure into the relationship between the influencing factors - Peng Wang; Wendi Zhang; Jiawen Liu; Pan He; Jiaming Wang; Lei Huang; Bing Zhang (Journal of Environmental Management, 2023)

Chlorine dioxide bleaching wastewater degradation in intimately coupled photocatalysis and functional bacteria: The roles of adsorption, photocatalysis, and biotransformation - Yinna Liang; Maman Galandi Abdoulaye; Chenxu Zhou; Bing Xiao; Jiaming Zhang; Jianhua Xiong; Qifeng Yang; J.R. Zhao; Shuangfei Wang (Journal of Cleaner Production, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Systematical site investigation and temperature sensing in Pr3+-doped M3RE4O9 (M = Sr and Ba; RE = Sc, Y, Lu) - Xiangyu Han; Changqing Hu; Jiaming Wu; Shuxian Wang; Zhengmao Ye; Qingchun Yang (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Design, synthesis and biological evaluation of indoline derivatives as multifunctional agents for the treatment of ischemic stroke - Shuaishuai Du; Fan Jin; Jiaming Li; Xiaodong Ma; Hongwei Wang; Shihu Qian (Medicinal Chemistry Research, 2022)

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

Occurrence and driving forces of different nitrogen forms in the sediments of the grass and algae-type zones of Taihu Lake - Zihan Zhao; Mingli Zhang; Jiaming Tian; Kangkang Yu; Yan Chen; Yanhua Wang (Environmental Science and Pollution Research, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Discovery of the Early Paleozoic Akechukesai high-Mg diorites in the western segment of East Kunlun Orogenic Belt and its constraints on the mechanism of break-off from Proto-Tethys oceanic subducted slab - Chao Wang; Fengyue Sun; Dongwei Liu; Lei Zuo; Tuofei Zhao; Jiaming Yan (Geosciences Journal, 2022)

Characteristics of PAHs in soils under different land-use types and their associated health risks in the northern Taihu Basin, China - Tian Sun; Yanhua Wang; Jiaming Tian; Xinggong Kong (Journal of Soils and Sediments, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Single-stranded DNA generated by high temperature accepts protons and builds up mutagenic and carcinogenic strong acids - Yuhan Lin; Xiaoxiao Zhang; Yuchuan Wang; Jiaming Zhang; Qiuyun Liu (Molecular Biology Reports, 2021)

A study on the effects of anion, cation, organic compounds, and pH on the release behaviors of As and Sb from sediments - Haibo Wang; Jiaming Xu; Mario Alberto Gomez; Zhongliang Shi; Yongfeng Jia (Environmental Science and Pollution Research, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Maneuverability and Hydrodynamics of a Tethered Underwater Robot Based on Mixing Grid Technique - Jiaming Wu; Shunyuan Xu; Hua Liao; Chenghua Ma; Xianyuan Yang; Haotian Wang; Tian Zhang; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
The maneuverability and hydrodynamic performance of the tethered underwater robot in a uniform flow field is investigated. In this research, a tethered underwater robot symmetrically installed with NACA66 hydrofoils and Ka 4-70/19A ducted propellers around its main body is first constructed. The method of overlapping grid combined with sliding mesh is applied in the numerical simulations, and the principle of relative motion is adopted to describe the hydrodynamic responses of the tethered underwater robot during the robot manipulation. The reliability of the CFD methods applied in this research is verified by experimental results, and the comparison between numerical and experimental ones shows that there is very little difference being found. The numerical results indicate that computational cost due to the research’s large-scale domain can be effectively reduced by the adopted numerical methods, hydrofoils’ control effect is greatly influenced by the towing speeds, and thrusts issued from the ducted propellers are related to the tethered underwater robot’s position and towing speed.

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

Corrosion Mechanism of 5083 Aluminum Alloy in Seawater Containing Phosphate - Jiaming Wang; Haodong Yang; Min Du; Jian Hou; Wenshan Peng; Cunguo Lin (Journal of Ocean University of China, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

A Risk Assessment Method for Metro Shield Tunnel Construction Based on Interval Number - Yeqin Zhang; Jiaming Zhang; Hailin Guo; Yang Zhou; Guofu Ma; Cong Wang (Geotechnical and Geological Engineering, 2020)

Double decomposition and optimal combination ensemble learning approach for interval-valued AQI forecasting using streaming data - Zicheng Wang; Liren Chen; Jiaming Zhu; Huayou Chen; Hongjun Yuan (Environmental Science and Pollution Research, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

CDKN1B Mediates Apoptosis of Neuronal Cells and Inflammation Induced by Oxyhemoglobin via miR-502-5p After Subarachnoid Hemorrhage - Dong Chen; Xianwei Wang; Jiaming Huang; Sifu Cui; Liqiang Zhang (Journal of Molecular Neuroscience, 2020)

Preliminary marine gravity field from HY-2A/GM altimeter data - Qiankun Liu; Ke Xu; Maofei Jiang; Jiaming Wang (Acta Oceanologica Sinica, 2020)

Gene Biomarkers Derived from Clinical Data of Hepatocellular Carcinoma - Jiaming Qi; Jiaxing Zhou; Xu-Qing Tang; Yaolai Wang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

High spatio-temporal heterogeneity of carbon footprints in the Zhejiang Province, China, from 2005 to 2015: implications for climate change policies - Sheng Zheng; Jiaming Shan; Ramesh P. Singh; Yuzhe Wu; Jiachen Pan; Yueshe Wang; Eric Lichtfouse (Environmental Chemistry Letters, 2020)

Dynamic Analysis of the Rock Burst Potential of a Longwall Panel Intersecting with a Fault - Lishuai Jiang; Peng Kong; Peipeng Zhang; Jiaming Shu; Qingbiao Wang; Lianjun Chen; Quanlin Wu (Rock Mechanics and Rock Engineering, 2020)

A conjugated mTOR/MEK bifunctional inhibitor as potential polypharmacological anticancer agent: the prototype compound discovery - Qiangqiang Tao; Fang Fang; Jiaming Li; Yong Wang; Can Zhao; Jingtai Liang; Xiaodong Ma; Hao Wang (Medicinal Chemistry Research, 2020)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)

Oxidative Damage Induced by Nano-titanium Dioxide in Rats and Mice: a Systematic Review and Meta-analysis - Hongmei An; Chunmei Ling; Mengchuan Xu; Mingjuan Hu; Haixia Wang; Jiaqing Liu; Guangling Song; Jiaming Liu (Biological Trace Element Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Effect of Fracture Heterogeneity on Rock Mass Stability in a Highly Heterogeneous Underground Roadway - Peng Kong; Lishuai Jiang; Jiaming Shu; Atsushi Sainoki; Qingbiao Wang (Rock Mechanics and Rock Engineering, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Stacked auto-encoder for classification of polarimetric SAR images based on scattering energy - Ronghua Shang; Yongkun Liu; Jiaming Wang; Licheng Jiao; Rustam Stolkin (International Journal of Remote Sensing, 2019)

Optimum removal conditions of aniline compounds in simulated wastewater by laccase from white-rot fungi - Bo Yang; Yacheng Wang; Zhiguo Liu; Jun Liu; Jiaming Cai (Journal of Environmental Health Science and Engineering, 2019)

Bank gully extraction from DEMs utilizing the geomorphologic features of a loess hilly area in China - Xin Yang; Jiaming Na; Guoan Tang; Tingting Wang; Axing Zhu (Frontiers of Earth Science, 2019)

Preparation of chitosan/Co-Fe-layered double hydroxides and its performance for removing 2,4-dichlorophenol - Bo Yang; Jun Liu; Zhiguo Liu; Yacheng Wang; Jiaming Cai; Lingjie Peng (Environmental Science and Pollution Research, 2019)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Integrated control of tobacco black shank by combined use of riboflavin and Bacillus subtilis strain Tpb55 - Chengsheng Zhang; Jiaming Gao; Teng Han; Xueying Tian; Fenglong Wang (BioControl, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

Soil heavy metal contamination related to roasted stone coal slag: a study based on geostatistical and multivariate analyses - De’an Li; Jianguo Jiang; Tianran Li; Jiaming Wang (Environmental Science and Pollution Research, 2016)

Genetic mapping and molecular marker development for Pi65(t), a novel broad-spectrum resistance gene to rice blast using next-generation sequencing - Wenjing Zheng; Yan Wang; Lili Wang; Zuobin Ma; Jiaming Zhao; Ping Wang; Lixia Zhang; Zhiheng Liu; Xiaochun Lu (Theoretical and Applied Genetics, 2016)

Removal of Pb and Zn from contaminated soil by different washing methods: the influence of reagents and ultrasound - Jiaming Wang; Jianguo Jiang; Dean Li; Tianran Li; Kaimin Li; Sicong Tian (Environmental Science and Pollution Research, 2015)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)

The Arg194Trp polymorphism in the XRCC1 gene and cancer risk in Chinese Mainland population: a meta-analysis - Jin Huang; Jie Zhang; Yuliang Zhao; Banghua Liao; Jiaming Liu; Ling Li; Mingheng Liao; Lanlan Wang (Molecular Biology Reports, 2011)

Contribution of the IBD5 locus to inflammatory bowel disease: a meta-analysis - Jian Wang; Xi Wang; Hong Yang; Dong Wu; Li Wang; Jiaming Qian (Human Genetics, 2011)

Attractive model and marketing implications of Theme Shopping Tourism destination - Jiaming Liu; Run Wang (Chinese Geographical Science, 2010)

Factors of spatial distribution of recreation areas in peri-urban Beijing - Jiaming Liu; Run Wang; Tian Chen (Journal of Geographical Sciences, 2010)